Characterization of new microsatellite loci in Pieris amamioshimensis (Ericaceae), a species nearly extinct in the wild. Issue 1 (12th October 2017) - Mitsui, Yuki; Nagasawa, Junichi; Maeda, Yoshiyuki; Setoguchi, Hiroaki
Abstract: A set of 11 polymorphic microsatellite markers has been developed and characterized for the critically endangered species Pieris amamioshimensis . Fifty‐nine individuals of an ex‐situ population were used to identify these markers. The total number of alleles for each locus ranged from 3 to 9, with an average of 5.4. The expected heterozygosities ( H S ) and observed heterozygosities ( H O ) ranged from 0.47 to 0.77 and 0.22 to 0.88, respectively. In total, four loci exhibited significant deviations from Hardy–Weinberg equilibrium: two loci showed significant heterozygosity excess and the other two loci showed significant heterozygosity deficit. The polymorphism information content (0.43 ≤ PIC ≤ 0.73), the probability of exclusions (PE1  = 0.9565, PE2  = 0.9969 and PE3  = 0.9999) and probabilities for identity (PI = 3.78 × 10 −9 and PI‐Sib = 2.35 × 10 −4 ) suggest that these markers are useful for estimating not only genetic diversity but also parentage, for the ex‐situ conservation management of populations. Abstract : The 11 novel polymorphic microsatellite markers were developed from P. amamioshimensis . They can be used for the study of genetic diversity and parentage analysis for the management of populations as ex ‐ situ conservation.